Investigating the mediating role of classroom achievement emotions in the relationship between school physical environment and physical literacy of adolescents - Xin Zang; Yizheng Wang; Chengkun Lu; Inae Yoon (Scientific Reports)
Abstract The issue of insufficient physical activity(PA) among adolescents is increasingly prominent, and Physical literacy (PL) is considered an important determinant of PA. This study aimed to explore the interplay between school physical environment, classroom achievement emotions and PL among adolescents.1,020 junior and senior high school students from 12 schools in Liaoning Province participated in the study(mean age = 15.23 ± 1.63) years. The collected data were analyzed using SPSS 27.0 and AMOS26.0, independent sample t-tests, Pearson correlation, linear regression, structural equation model testing and mediation analysis were used to analyze the relationship between indicators. The findings indicated significant correlations existed among the school physical environment, classroom achievement emotions, and PL. Regression analyses showed that both the school physical environment and classroom achievement emotions significantly predicted PL. Structural equation modeling analysis demonstrated that the school physical environment directly influenced PL (β = 0.259, 95% CI [0.164, 0.370]. Furthermore, classroom achievement emotions mediated the indirect effect of the school physical environment on PL (β  = 0.685, 95% CI [0.598, 0.774].This study provides evidence of the relationships among school physical environment, classroom achievement emotions, and PL. This study traces to the source both external environmental and internal psychological factors that promote adolescents’ PL. The findings suggest that creating diverse and suitable school physical environment, alongside positive classroom achievement emotions, constitutes an effective path for enhancing adolescents’ PL cultivation.